Transcriptome sequencing analysis of echovirus 30 infection reveals its potential pathogenesis - Sun, Qiang; Li, Jichen; Zhang, Bo; Wang, Rui; Wang, Congcong; Li, Xiaoliang; Liu, Ying; Zhang, Yong (Frontiers in Microbiology, 2022)
Echovirus 30 (E30) causes various diseases, such as viral encephalitis; aseptic meningitis; hand, foot, and mouth disease; and acute flaccid paralysis. Related neurological infections are most concerning. However, the molecular mechanisms of E30 pathogenesis are not fully understood. There is a growing research interest in E30 as a cause of neurological disease. The present study aims to describe E30 infection, especially the changes in differential factor expressions after infection, in human glioma (U251) cells and mice brains using transcriptome sequencing analysis. Clear changes in the gene expression of factors associated with the defense response to viruses, inflammation-related signaling pathways, and neurological complication- related pathways were observed. Our results suggest that after E30 infection, the genes related to immune response were induced in the human glioma cells and mice brains, whereas genes functioning in the development and function of neural tissue were inhibited. Overall, our study successfully established E30 infection of U251 and mouse brain tissue and profiled the infection-induced changes in cellular and organizational transcriptomes and revealed the molecular level changes during E30 infection.